2015
DOI: 10.3390/e17042367
|View full text |Cite
|
Sign up to set email alerts
|

An Entropy-Based Network Anomaly Detection Method

Abstract: Data mining is an interdisciplinary subfield of computer science involving methods at the intersection of artificial intelligence, machine learning and statistics. One of the data mining tasks is anomaly detection which is the analysis of large quantities of data to identify items, events or observations which do not conform to an expected pattern. Anomaly detection is applicable in a variety of domains, e.g., fraud detection, fault detection, system health monitoring but this article focuses on application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 102 publications
(117 reference statements)
3
92
0
2
Order By: Relevance
“…Average score method As shown in Figure 3, this research applied entropy weighted sums to confirm the compared GMM results and proposes another alternative method to enrich the quantitative analysis of the GMM levels [66,67]. As shown in Figure 3, this research applied entropy weighted sums to confirm the compared GMM results and proposes another alternative method to enrich the quantitative analysis of the GMM levels [66,67].…”
Section: Iab Gmm Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average score method As shown in Figure 3, this research applied entropy weighted sums to confirm the compared GMM results and proposes another alternative method to enrich the quantitative analysis of the GMM levels [66,67]. As shown in Figure 3, this research applied entropy weighted sums to confirm the compared GMM results and proposes another alternative method to enrich the quantitative analysis of the GMM levels [66,67].…”
Section: Iab Gmm Data Collectionmentioning
confidence: 99%
“…The theoretical framework of this research is shown in Figure 2, and the corresponding research steps are illustrated in Figure 3. As shown in Figure 3, this research applied entropy weighted sums to confirm the compared GMM results and proposes another alternative method to enrich the quantitative analysis of the GMM levels [66,67].…”
Section: Analysis Levelmentioning
confidence: 99%
“…Entropy method [41] is an objective empowerment approach used to reflect the disorder degree of information in information theories, which now has been expanded to social and economic areas [40,41,47,98,99]. The weights of individual indicators are determined by calculating the entropy and entropy weight of each of them.…”
Section: Entropy Weightmentioning
confidence: 99%
“…The entropy method [50][51][52] is an objective approach reflecting the disorder degree of information in not only information theory but also in the expansion of social and economic areas [50,51,[53][54][55] where the weights of individual indicators are determined by calculating the entropy and entropy weight. The greater the entropy is, the smaller the corresponding entropy weight.…”
Section: Methodsmentioning
confidence: 99%